Synthesis of talc/Fe3O4 magnetic nanocomposites using chemical co-precipitation method. - Kalantari, Katayoon; Ahmad @ Ayob, Mansor; Shameli, Kamyar; Khandanlou, Roshanak (Dove Medical Press, 2013)
The aim of this research was to synthesize and develop a new method for the preparation of iron oxide (Fe3O4) nanoparticles on talc layers using an environmentally friendly process. The Fe3O4 magnetic nanoparticles were synthesized using the chemical co-precipitation method on the exterior surface layer of talc mineral as a solid substrate. Ferric chloride, ferrous chloride, and sodium hydroxide were used as the Fe3O4 precursor and reducing agent in talc. The talc was suspended in deionized water, and then ferrous and ferric ions were added to this solution and stirred. After the absorption of ions on the exterior surface of talc layers, the ions were reduced with sodium hydroxide. The reaction was carried out under a nonoxidizing oxygen-free environment. There were not many changes in the interlamellar space limits (d-spacing=0.94-0.93nm); therefore, Fe3O4 nanoparticles formed on the exterior surface of talc, with an average size of 1.95-2.59nm in diameter. Nanoparticles were characterized using different methods, including powder X-ray diffraction, transmission electron microscopy, emission scanning electron microscopy, energy dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy. These talc/Fe3O4 nanocomposites may have potential applications in the chemical and biological industries.